2021
DOI: 10.1111/dar.13425
|View full text |Cite
|
Sign up to set email alerts
|

Why do women consume alcohol during pregnancy or while breastfeeding?

Abstract: Issue. Alcohol consumption during pregnancy and breastfeeding cause adverse health outcomes to the mother and child, including Fetal Alcohol Spectrum Disorder (FASD). Approach. Systematic literature review and thematic synthesis. Original studies that contained reasons for alcohol consumption in pregnancy and while breastfeeding were included. The Mixed Methods Appraisal Tool (MMAT) and the Confidence in the Evidence of Reviews of Qualitative Research (CerQUAL) approach were utilised. The review protocol is av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 89 publications
(307 reference statements)
2
32
0
3
Order By: Relevance
“…In the present study, more than 80 % of mothers drank tella during lactation for a variety of reasons including optimising breast milk production. This is consistent with a finding reported by a recent review article, Popova and colleagues (35) . However, a systematic review has indicated that alcohol consumption resulted in a decrease in total breast milk yield (36) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, more than 80 % of mothers drank tella during lactation for a variety of reasons including optimising breast milk production. This is consistent with a finding reported by a recent review article, Popova and colleagues (35) . However, a systematic review has indicated that alcohol consumption resulted in a decrease in total breast milk yield (36) .…”
Section: Discussionsupporting
confidence: 94%
“…As noted by a prior study, prenatal alcohol exposure was associated with growth restrictions in weight and height, which is largely determined by birth. These growth restrictions are a particular problem among children born to women with alcohol abuse and/or dependence (34,35) . This may be because alcohol passes the placental barrier and allows alcohol to reach the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, alcohol is not only the most commonly used drug by females of reproductive age (24.4% prevalence), but Kanny et al (2013) found that approximately 12.5% of women continue to drink at binge levels (4+ drinks in 2 h) during pregnancy, resulting in high BECs (0.08% or greater) in relatively short periods of time ( Kanny et al, 2013 ). Investigations into this continuance of alcohol use by women both during pregnancy and while breastfeeding despite alcohol’s known teratogenicity have revealed a complex interplay of factors influencing this ongoing prevalence in behavior, including but not limited to societal pressure, internal and external stress, alcohol dependence, poor understanding of scientific data on substance use during pregnancy, and even inaccurate advice from medical practitioners ( Latuskie et al, 2019 ; Hernandez et al, 2021 ; Popova et al, 2021 ). These findings highlight the importance of greater dissemination scientific data on alcohol’s teratogenicity to lay populations and medical practitioners.…”
Section: Fetal Alcohol Spectrum Disorder (Fasd) and The Lasting Devel...mentioning
confidence: 99%
“…Most qualitative approaches in addiction and substance use research and health services research use interviews or focus-groups, especially in the German research context (Ullrich et al, 2022) This is also reflected in the two reviews that included qualitative studies using telephone interviews, face-to-face interviews or focus-groups (Hammer & Rapp, 2022;Popova et al, 2022). Only three studies by Toutain (2010Toutain ( , 2013Toutain ( ,2017 from France used internet forums or chat groups as a data source.…”
Section: Strengths and Challenges Of Both Data Collection Methodsmentioning
confidence: 99%
“…Little is known about alcohol consumption during pregnancy and how it is related to perceptions of motherhood in Germany. In very recent literature reviews which centred on alcohol consumption during pregnancy ( Hammer & Rapp, 2022 ) and self-reported reasons for alcohol consumption during pregnancy ( Popova et al, 2022 ), no studies from Germany were found. Apart from the study by our research group, we are also not aware of any studies (neither qualitative nor quantitative) from Germany.…”
Section: Introductionmentioning
confidence: 99%